Red Betel Leaf Bioactive Compounds as ERα Receptor Inhibitors In Silico and MCF-7 Cell Anticancer In Vitro - Ayu Tri Nursyarah; Mega Safithri; Dimas Andrianto (Bogor Agricultural University, Indonesia, 2023)
Cancer is one of the leading causes of death in the world. Excess endogenous estrogen is a risk factor for breast cancer. Red betel leaf herbal plants have been used as an alternative cervical and colon cancer treatment. This study aimed to obtain the active compounds that play a role in ERα receptor inhibitors in silico and to determine the anti-breast cancer cytotoxic activity of the extract and fraction of red betel leaf against MCF-7 cells. We use in silico research method using the YASARA Structure software with anti-breast cancer receptors, namely 3ERT, and in vitro using the MTT test on the anti-breast cancer cytotoxic activity of MCF-7 cells. There are 38 compounds that were obtained from the research. The results of the in silico test showed that the bioactive compound that played a role in inhibiting the ERα was 2-(4-Hydro xyphenyl)-2-phenyl-N(3,3-diphenylpropyl)-acetamide (44578655), a compound from water fraction, with an inhibition constant of 2.82 × 10-8 µM and Gibbs free energy of –10.2880 Kcal/mol. In vitro results showed that the best cell growth inhibition value was obtained from the n-hexane fraction at a concentration of 500 ppm of 73.42%. The conclusions of this study indicate that the bioactive compound of red betel leaf is water fraction is the best fraction inhibition. However, the hexane fraction proved to have cytotoxic activity against breast cancer MCF-7 cells.